Green-synthesis of Silver Nanoparticles by Hygrophila auriculata Extract: Innovative Technique and Comprehensive Evaluation - Nayak, Smita; Ghugare, Priyanka; Vaidhun, Bhaskar (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Metal nanoparticles are of great scientific interest as they bridge the gap between the bulk and atomic structures. A number of methods of synthesizing nanoparticles have been developed and can be grouped into top-down (physical), bottom-up (chemical) and biological methods. Physical methods are expensive due to continuous consumption of energy to maintain the high pressure and temperature employed in nanoparticle synthesis and requires highly sophisticated equipment. In the chemical synthesis of nanoparticles, generation of hazardous by-products as well as involvement of certain chemicals that are environmental contaminants is a major concern. As against this plant-mediated synthesis of nanoparticles employs green synthetic route, is clean, ecofriendly, cost effective, safe, convenient and beneficial technique for large-scale production of nanoparticles. Aim: The study focuses on green synthesis of silver nanoparticles using plant extract as reducing, capping and stabilizing agents. It has been reported that aqueous silver ions when exposed to plant leaf extract undergo reduction leading to formation of silver nanoparticles. Methods: In present study, silver nanoparticles were synthesized by using hydro alcoholic extract of Hygrophila auriculata whole plant as reducing agent. Results: Synthesis of silver nanoparticles was confirmed by UV spectroscopy, particle size analysis, zeta potential determination, Fourier Transform Infrared Resonance, X-Ray Diffraction, Scanning Electron Microscopy and Transmission Electron Microscopy. Conclusion: Plant mediated nanoparticle synthesis is a simple, reproducible and ecofriendly method for elucidation of silver nanoparticles. Data obtained reveals the role of hydro alcoholic extract of Hygrophila auriculata in silver nanoparticle synthesis.
Keywords: Green synthesis; Silver nanoparticles; Hygrophila auriculata; Characterization; Surface Plasmon resonance